Evaluation des Freiburger Einsilbertests im Störschall = Evaluation of the Freiburg monosyllabic speech test in background noise - Löhler, Jan; Akcicek, B.; Pilnik, M.; Saager-Post, K.; Dazert, Stefan; Biedron, S.; Oeken, J.; Mürbe, D.; Löbert, J.; Laszig, Roland; Wesarg, T.; Langer, C.; et al. (HNO, 2013)
Schwerhörigkeit; Sprachaudiometrie; Einsilbertest; Störschall; Hörgeräte
Online publiziert: 19. Oktober 2012
Gesehen am 19.05.2021